Seasonal and Spatial Variability of Carbon Monoxide (CO) in the Martian Atmosphere From PFS/MEX Observations. Issue 2 (23rd February 2021) - Bouche, Jimmy; Coheur, Pierre‐François; Giuranna, Marco; Wolkenberg, Paulina; Nardi, Luca; Amoroso, Marilena; Vandaele, Ann Carine; Daerden, Frank; Neary, Lori; Bauduin, Sophie
Abstract: A subset of more than 100, 000 nadir measurements covering more than 7 Martian years (MY 26–MY 33) recorded in the thermal part of the Short Wavelength Channel (SWC) from the Planetary Fourier Spectrometer (PFS) on board Mars Express is exploited to investigate the global distribution and the seasonal cycle of carbon monoxide (CO) on Mars. The retrieval of CO vertical profiles is successfully achieved using a methodology based on the optimal estimation but the low information content is such that we mainly discuss the variability in CO in terms of integrated columns (from the surface to 24 km) or the associated column‐averaged mixing ratio. We find a strong seasonality in CO, especially at mid and high‐latitudes, which confirms earlier work and the current knowledge of the CO2 condensation/sublimation cycles, as implemented for instance in the Global Environmental Multiscale (GEM) general circulation model for Mars, that we use as a basis for comparison. We report a general consistency between model and observation, with a tendency of the latter to provide lower CO volume mixing ratios (VMRs), except at low latitudes. The spatial distribution of the CO column‐averaged VMR is obtained on a seasonal basis and investigated in terms of large‐scale patterns but also local peculiarities. Finally, we show that the retrieved profiles systematically present strong CO vertical gradients close to the surface in mid‐ and equatorial latitudes, likely related to the vertical sensitivity of PFS rather than real near‐surface CO enrichment. Plain Language Summary: The atmosphere of Mars is mainly composed of carbon dioxide (∼95%) and other carbon compounds in much lower concentration, including carbon monoxide (CO). The relative abundances of the carbon compounds depend on each other and they vary during a Martian year primarily according to the temperature cycle. In the colder periods carbon dioxide indeed freezes (mainly at the polar caps), while it sublimates under higher temperatures, causing large variations to atmospheric pressure and the volume mixing ratio of the trace species. This study examines the variability of CO in the low atmosphere of Mars (from the surface to 24 km), on a global scale. The CO seasonal cycle is obtained by exploiting ∼100, 000 observations made by the Planetary Fourier Spectrometer (PFS) on‐board the Mars Express satellite in almost aerosol‐free conditions. For each individual PFS observation, a CO vertical profile is retrieved. The resulting column distributions and time evolutions, showing large variability especially at mid and high latitudes, are in good agreement with previous work as well as with simulated distributions from a state‐of‐the‐art chemistry‐transport model. Key Points: Planetary Fourier Spectrometer observations are used to investigate the global distribution and the seasonal cycle of carbon monoxide (CO) on Mars in weak dust conditions The seasonal cycle is driven by the sublimation/condensation of CO2, with a large variability around a mean CO volume mixing ratio of about 820 ppm The distribution and temporal evolution agree generally well with previous observations and with simulations from the Global Environmental Multiscale ‐Mars model